Ten Fallacies of University Social Responsibility - Vallaeys, François (2018)
This article aims at consolidating the theoretical framework of University Social Responsibility (USR) based on the conceptual analysis of the ten more common fallacies regarding the meaning of this university trend, from the Latin American standpoint. This allows to define the conceptual progress reached since the beginning of the 21st century regarding the triple dimension of the ethical principles governing USR, the social transformation objective beneath it, and the cross-sectional management policy that makes it possible, without falling into a general reductionism that takes it for a mere declaratory commitment, a series of good practices, an enterprise ideology, a trivial instrumental management strategy, or an expression of self-indulgence of university authorities. The critical explanations contribute additionally to the debate on the pertinence of USR prizes flourishing at present, in contrast with the legal frameworks that now impose social responsibility on higher education. It can be concluded that the remarkable progress in USR in Latin America demands seriousness in its definition.